Accounting for Business Combinations. - Phillips, Lawrence C. (The Accounting Review, 1965)
Abstract This article focuses on the accounting criteria for judging the economic realities and the intent of the parties to a business combination. The present accounting criteria for judging the economic realities and the intent of the parties to a business combination are inadequate. The reduced importance of the relative-size criterion has resulted in an indiscriminate use of the pooling concept. Effective control over the assets, management, and ownership of the succeeding entity is more important in the determination of economic reality than is a theory based upon a proportional continuation of the former interests. The purchase concept adequately conforms to the requirements of accounting regarding asset realization and objectivity. A merger proposal is merely a specialized form of capital-budgeting decision. Consequently, all alternatives to the merger proposal should be considered. If a firm wishes to maximize conventionally reported earnings, the pooling basis may be misleading and result in the acceptance of undesirable investment proposals.